Risk factors of mortality in children with acquired prothrombin complex deficiency at Dr. Zainoel Abidin General Hospital,Banda Aceh - Munawarah, Syifa; Sovira, Nora; Anidar, Anidar; Herdata, Heru Noviat; Edward, Eka Destianti; Ismy, Jufitriani (Paediatrica Indonesiana, 2025)
Background  Acquired prothrombin complex deficiency (APCD) is a rare but life-threatening bleeding disorder in children. Intracranial hemorrhage (ICH) is the leading cause of death, with an estimated risk affecting 50–80% of cases. Key risk factors associated with mortality in APCD include onset of disease, presence of ICH, and the initial Glasgow Coma Scale (GCS) score. Routine intramuscular administration of vitamin K at birth has been shown to effectively prevent early and late-onset vitamin K deficiency bleeding. However, in settings where vitamin K prophylaxis is not administered or is delayed, the risk of APCD increases significantly. Despite these concerns, other potentially relevant clinical factors contributing to APCD outcomes remain under-investigated. Objective To identify risk factors associated with APCD mortality in children treated at Dr. Zainoel Abidin General Hospital, Banda Aceh. Methods This cross sectional study analyzing children diagnosed with APCD at Dr. Zainoel Abidin General Hospital from October 2022 to October 2024. Data were collected from the medical records of 30 children and analyzed using Chi-square and logistic regression tests. Results This study included 30 subjects, the majority of whom were male and aged 8 days to 6 months. Most of subject were born full term, delivered vaginally, and had birth weight ≥ 2.500 grams. Notably, 25/30 children did not receive vitamin K prophylaxis, 14/18 children were exclusively breastfed without vitamin K prophylaxis, and 25/30 children had good nutritional status. Late-onset APCD was observed in 14 out of 30 cases.  Intracranial vs extracranial hemorrhage was occurred in 21 vs 9 children. Initial GCS scores ≤ 8 at initiation of treatment were noted in 11/30 children. The mortality rate was occurred in 12/30 subjects (40%). Chi-square analysis revealed significant associations between increased mortality and late onset APCD (P=0.030), ICH (P=0.049), and initial GCS score ≤ 8 (P=0.009). Logistic regression analysis revealed initial GCS score was associated with the highest risk of mortality in APCD, with a 16-fold increase in risk (P=0.022; OR 15.9; 95%CI 1.5 to 168.9). Conclusion Intracranial hemorrhage, late-onset APCD, and initial GCS scores ≤ 8 are significantly associated with increased APCD mortality, with initial GCS emerging as the most influential risk factor.